RIFM fragrance ingredient safety assessment, 2-octyldodecan-1-ol, CAS Registry Number 5333-42-6. (December 2019) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: 2-Octyldodecan-1-ol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.